A Systemic Mapping Approach for Right and Left Parahisian Ventricular Arrhythmias Ablation - Kong, Ling-cong; Shuang, Tian; Li, Zheng; Zou, Zhi-guo; Jiang, Wen-long; Pu, Jun; Wang, Xin-hua (Frontiers in Cardiovascular Medicine, 2022)
Background: Catheter ablation for parahisian ventricular arrhythmias (PHVA) is technically challenging and associated with increased risks of atrioventricular block (AVB). We developed a systemic mapping approach to improve the efficacy and safety of PHVA ablation. Methods: Forty-three patients (29 males; average age 65.8 ±10.5 years) with PHVAs were enrolled. A systemic mapping approach comprising differential electrocardiogram, sequential mapping and ablation beneath/above the septal leaflet of the tricuspid valve (SLTV) and at the neighboring/contralateral regions (the aortic root and sub-aortic valve region) was applied for PHVA. The effectiveness and safety of this approach was evaluated at one year’s follow-up. Results: Sequential ablation beneath the SLTV (B-SLTV) succeeded in 24 (66.7 %) of 36 with right PHVA and ablation above the SLTV succeeded in 6 of the remaining 12 with failed B-SLTV ablation. Target-His bundle (HB) distance > 4.5 mm significantly predicted successful right PHVA ablation (OR 1.703; 95% CI 1.084-2.676, P=0.02). “Seeming” right PHVA by electrocardiogram in 4 and apparent left PHVA in 3 was successfully ablated at the sub-aortic parahisian region. At one year’s follow-up, 27 (75%) of 36 patients with right PHVA and 6 (85.7%) of 7 patients with left PHVA were free of PHVA recurrence off anti-arrhythmic drugs. The total success rate was 76.7% by using the systemic mapping approach for PHVA. One patient with A-SLTV ablation underwent pacemaker implantation due to complete AVB. Conclusions: The systemic mapping approach was effective and safe for treating PHVA. The target-HB distance was a significant predictor for right PHVA ablation.